2018
DOI: 10.1111/aej.12280
|View full text |Cite
|
Sign up to set email alerts
|

pH changes in radicular dentine associated with calcium hydroxide and corticosteroid/antibiotic pastes

Abstract: The aim was to compare hydroxyl ion diffusion through dentine following placement of calcium hydroxide and Ledermix paste. Thirty-six teeth were divided into one control (n = 6) and three experimental (n = 10) groups - (i) Pulpdent paste; (ii) Pulpdent/Ledermix pastes; (iii) Ledermix paste and (iv) Saline. pH was measured in inner and outer dentine cavities over 12 months. Inner dentine time to maximum pH (T ) was 1 week for Pulpdent and 2 weeks for Pulpdent/Ledermix. Pulpdent's outer dentine T was 4 weeks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…25 Therefore, the use of H 2 O 2 as an intracoronal bleaching agent decreased extraradicular pH all groups. This study suggests that was a pH change of the external medium, in agreement with the results of Rokaya et al, 25 de Sá et al, 26 and Lou et al 27 Cai et al 28 and Mustafa et al 29 found that the pH of the dentin increases after placing calcium hydroxide Ca(OH) 2 in the root canal. de Sá al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…25 Therefore, the use of H 2 O 2 as an intracoronal bleaching agent decreased extraradicular pH all groups. This study suggests that was a pH change of the external medium, in agreement with the results of Rokaya et al, 25 de Sá et al, 26 and Lou et al 27 Cai et al 28 and Mustafa et al 29 found that the pH of the dentin increases after placing calcium hydroxide Ca(OH) 2 in the root canal. de Sá al.…”
Section: Discussionsupporting
confidence: 90%
“…Cai et al 28 and Mustafa et al 29 found that the pH of the dentin increases after placing calcium hydroxide Ca(OH) 2 in the root canal. de Sá al.…”
Section: Discussionmentioning
confidence: 99%